Comparison of Pregnancy and Neonatal Outcomes in Frozen and Fresh Embryo Transfer in ART Cycles: A Retrospective Cohort Study - Mahsomeh Hajishafiha; Tahere Behrouzi lak; Vahideh Nobakht; Nahid Sadegh Asadi; Sima Oshnouei; Fedyeh Haghollahi (Mashhad University of Medical Sciences, 2020)
Background & aim: In addition to the benefits of frozen embryo transfer (FET), the key question is whether freezing or melting embryos can cause fetal harm and prenatal complications. This study aimed to assess pregnancy and neonatal outcomes after FET and fresh embryo transfer (ET). Methods: This retrospective cohort study investigated the pregnancy outcomes of infertile women undergoing intracytoplasmic sperm injection with FET and ET in Kowsar Infertility Center of Motahary hospital in Urmia, Iran between March 2014 and March 2016. A questionnaire was completed based on the hospital records of pregnancy or neonatal outcomes. To assess the continuation of pregnancy and delivery, the questionnaires were completed through phone call. The pregnancy and neonatal outcomes were compared between FET (n=96) and fresh ET (n=93) using Student's t-test, Chi-square, Fisher's exact tests and multiple logistic regression using SPSS software (version 21.0). Results: The rate of ongoing pregnancy were reported as 60.2% and 76% in the FET and fresh ET groups, respectively. The rate of multiple pregnancy and ongoing pregnancy were lower in FET, compared to those reported for fresh ET (OR=0.38, 95% CI: 0.18-0.79, P=0.01; OR=0.48, 95% CI: 0.25-0.85, P=0.02). The frequency of spontaneous abortion was not different between two groups (P=0.07). The FET and fresh ET increased the odds of lower neonatal weight; however, it was not statistically significant. Conclusion: In this study, a lower rate of ongoing pregnancy was reported in the FET group. It seems that FET can cause damage to the embryo during freezing and melting.